Globalisation and public health: economic aspects - Phua, K.L. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2002)
Globalisation is affecting all aspects of human society. There is increasing economic integration of the countries of the world through trade and investment flows. There is also the spread of socio-cultural influences through education, the mass media and population movements. Globalisation is also affecting healthcare institutions as well as the health of the public. This paper, will discuss certain economic effects of globalisation that impact upon the health of the public. These include the following: population movements, the pharmaceutical industry, foreign investment in healthcare services, the international drug trade (legal drugs such as tobacco as well as illegal drugs), cross-border pollution and the “export of hazard”, the mass media and its effect on health-related behaviour, worldwide weather changes, “structural adjustment programmes” (SAPs) implemented in response to economic crises, and the impact of multilateral organizations on national health policy.